Modern Art and the Object : A Century of Changing Attitudes. - Johnson, Ellen H. (New York : Icon Editions - Harper Collins Publishers, 1995)
Acconci, Vito ; Albers, Josef ; Andersen, Hans Christian ; Andre, Carl ; Antin, Eleanor ; Arman ; Arp, Hans (Jean) ; Bacon, Francis ; Baldessari, John ; Balla, Giacomo ; Bannard, Darby ; Barry, Robert ; Baxter, Iain ; Beckett, Samuel ; Bergson, Henri ; Beuys, Joseph ; Bierstadt, Albert ; Blanche, Jacques-Emile ; Bochner, Mel ; Bonnard, Pierre ; Bontecou, Lee ; Brancusi, Constantin ; Braque, Georges ; Brecht, George ; Breton, André ; Bryant, William Cullen ; Burden, Chris ; Buren, Daniel ; Burgin, Victor ; Cage, John ; Casilear, John ; Cézanne, Paul ; Champney, Benjamin ; Cheret, Jules ; Christo ; Church, Frederic Edwin ; Close, Chuck ; Cole, Thomas ; Constable, John ; Copley, John Singleton ; Cornell, Joseph ; Courbet, Gustave ; Dali, Salvador ; Davis, Stuart ; Degas, Edgar ; Delacroix, Eugène ; Delaunay, Robert ; Denes, Agnes ; Dibbets, Jan ; Diebenkorn, Richard ; Dine, Jim ; Duchamp, Marcel ; Durand, Asher ; Eliot, T.S. ; Riverhead (New York) ; Fox, Terry ; Frankenthaler, Helen ; Fry, Roger ; Gauguin, Paul ; Gibson, John ; Gilbert & George ; Giotto ; van Gogh, Vincent ; Golding, William ; Goodnough, Robert ; Gorky, Arshile ; Gottlieb, Adolph ; Goya ; Graham, Dan ; Greenberg, Clement ; Guggenheim, Peggy ; Haacke, Hans ; Hanson, Duane ; Harrison, Newton ; Harrison, Wallace K. ; Heizer, Michael ; Hess, Thomas B. ; Hesse, Eva ; Hinman, Charles ; Hiroshige, Ando ; Hofmann, Hans ; Homer, Winslow ; Huebler, Douglas ; Insley, Will ; Ionesco, Eugène ; Jacquet, Alain ; Janis, Sidney ; Jensen, Alfred ; Johns, Jasper ; Johnson, Ray ; Judd, Donald ; Jung, Carl Gustav ; K'uan, Fan ; Kaltenbach, Steve ; Kandinsky, Wassily ; Kaprow, Allan ; Kensett, John Frederick ; Kirchner, Ernst Ludwig ; Klee, Paul ; Klein, Yves ; Kline, Franz ; de Kooning, Willem ; Kosuth, Joseph ; etc.
boek